Unveiling South African insect diversity: DNA barcoding’s contribution to biodiversity data - Stewart, Ross D.; van der Bank, Michelle; Davies, T. Jonathan (South African Journal of Science, 2024)
Insects are one of the most species-rich groups on Earth. They comprise much of animal diversity and play vital roles in ecosystems, including pollination, pest control, and decomposition. However, only a fraction of this diversity has been formally described. South Africa is recognised as one of the most biologically diverse countries globally, with an estimated 44 000 insect species. Many crops rely on insect pollinators, including canola, apples, oranges, and sunflowers. A shortage of wild pollinators currently threatens crop yields, yet our knowledge of insect diversity within South Africa is sparse. There are few taxonomic specialists relative to South Africa’s biodiversity, and the methods used for insect identification can be time-consuming and expensive. DNA barcoding provides an important research tool to accelerate insect biodiversity research. In this review, we queried the public DNA barcoding BOLD (Barcode of Life Data System) database for records of “Insecta” within South Africa, and 416 211 published records assigned to 28 239 unique BINs (Barcode Index Numbers) were returned. We identified five taxonomic orders with more BINs than known species in southern Africa (Hymenoptera, Diptera, Thysanoptera, Plecoptera, and Strepsiptera). Most of the barcoded records were derived from Malaise trap sampling in Gauteng, Mpumalanga and Limpopo, while the rest of South Africa remains poorly sampled. We suggest that there is a need for a comprehensive national sampling effort alongside increased investment in taxonomic expertise to generate critical baseline data on insect biodiversity before species are lost to extinction. Significance: Insects provide critical ecosystem services, but our knowledge of insect biodiversity is limited. DNA barcoding can help fill biodiversity knowledge gaps; however, within South Africa, sampling has been uneven. Well-sampled provinces include Gauteng, Mpumalanga and Limpopo, while the Eastern Cape, Free State, KwaZulu-Natal, Northern Cape, North-West and Western Cape remain under-sampled. We argue for a broad national Malaise trapping effort to generate crucial baseline data on insect biodiversity. Without urgent investment in taxonomic expertise and biomonitoring, we risk losing much of our biodiversity before it is even described.